Roles of AIM2 Gene and AIM2 Inflammasome in the Pathogenesis and Treatment of Psoriasis - Wang, Jieyi; Gao, Jing; Huang, Cong; Jeong, Sohyun; Ko, Randy; Shen, Xue; Chen, Chaofeng; Zhong, Weilong; Zou, Yanfen; Yu, Bo; Shen, Changbing (Frontiers in Genetics, 2022)
Psoriasis is an immune-mediated chronic inflammatory skin disease caused by a combination of environmental incentives, polygenic genetic control, and immune regulation. The inflammation-related gene melanoma deficiency factor 2 (AIM2) was identified as a susceptibility gene for psoriasis. The protein AIM2 combined with PYD-linked apoptosis-associated speck-like protein (ASC) and Caspase-1 form the AIM2 inflammasome, promoting the maturation and release of inflammatory cytokines such as IL-1β and IL-18, which in turn triggers an inflammatory response. Studies showed the associations between AIM2 and psoriasis. AIM2 has an essential role in the pathogenesis of psoriasis, and the inhibitors of AIM2 inflammasome will be new therapeutic targets for psoriasis. In this review, we summarized the roles of AIM2 gene and AIM2 inflammasome in pathogenesis and treatment of psoriasis, hopefully providing a better understanding and new insight into the roles AIM2 and AIM2 inflammasome in psoriasis.